PENGARUH PUPUK KANDANG SAPI DAN NPK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG MERAH (Allium ascalonicum L.) ASAL BIJI - Silvina, Fetmi; Yoseva, Sri; Sinambela, Flora Krisdyanti (Agros Journal of Agriculture Science, 2024)
spice vegetable and has long been intensively cultivated. Shallot productivity in Riau Province is relatively low due to low soil fertility. Efforts to increase shallot productivity can be done through fertilization, one of which is by applying a combination of cow manure and NPK. This research aims to determine the interaction of giving cow manure and NPK fertilizer and the influence of each factor on the growth and production of shallot from seed. The research was carried out in thr experimental garden of the Faculty of Agriculture, Riau University experimentally according to a completely randomized design (CRD), consisting of 2 factors. Factor I is cow manure with 3 levels: S0= 0 t.ha-1, S1= 7.5 t.ha-1, S3= 15 t.ha-1, and Factor II was NPK fertilizer with 3 levels: N1= 100 kg.ha-1, N2= 200 kg.ha-1, N3= 300 kg.ha-1. Thel data obtainedl were analyzed statisticallyl using analysisl of variancel and continuedl with Duncan's multiple  range testl at the 5% level using the SAS application. Parameters observed included plant height, number of leaves, number of tubers, number of tubers per hill, fresh weight of tubers per plot and weight of tubers suitable forstorage per plot. The result showed that the combination of cow manure and NPK increased the growth and production of shallots in all parameters. The combination of 15 t.ha-1 cow manure with 200 kg.ha-1 NPK fertilizer showed the best growth and production compared  to other treatments.